Fine control of particle size by seeding and ageing under agitation in the synthesis of analcime zeolite - Park, Soon Hee; Kim, Jong-Ho; Chung, Chang-Bock; Seo, Gon (The Korean journal of chemical engineering, 2015)
The size of analcime particles produced through hydrothermal reactions of alkaline synthesis mixtures was finely controlled by seeding and ageing under agitation. Adding acid-treated analcime seeds to the synthesis mixture followed by ageing in an agitated vessel facilitated further nucleation, which resulted in the formation of fine analcime particles with an extremely narrow size distribution. The size of analcime particles could be controlled in the range of 0.5-5.0 µm with a standard deviation of less than 0.1 µm by varying the amount and type of the acid-treated seeds, the ageing time, and the agitation speed.